Right ventricular monophasic action potentials in patients with long QT syndrome. - Gavrilescu, S (1978)
In 3 patients with the long QT syndrome, one caused by quinidine and 2 of congenital origin, right ventricular monophasic action potentials were excessively prolonged and of varying shapes in different recording sites. In addition, effective refractory periods of the ventricular muscle were abnormally long.